2016
DOI: 10.1167/iovs.16-20498
|View full text |Cite
|
Sign up to set email alerts
|

Author Response: Comments on Enrichment of Macular Pigment Enhances Contrast Sensitivity in Subjects Free of Retinal Disease: CREST - Report 1

Abstract: We note the letter from Professors Richard Bone and John Landrum 1 in response to our recently published clinical trial entitled ''Enrichment of Macular Pigment Enhances Contrast Sensitivity in Subjects Free of Retinal Disease: Central Retinal Enrichment Supplementation Trials -Report 1'' 2 and we thank our colleagues for their positive comments on our study. We acknowledge also their concerns about our Figure 1, which was prepared and included in our manuscript to help with the description of what we know abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition, lower zeaxanthin to lutein ratios are reported for groups at risk of age-related macular degeneration (e.g., the elderly and females) [74]. A number of studies, including some in healthy subjects, have demonstrated that lutein/zeaxanthin supplementation can improve visual performance, including contrast sensitivity, glare tolerance and photo stress recovery [65,66,67,68,69,70,71,72,75,76].…”
Section: Eye Disordersmentioning
confidence: 99%
“…In addition, lower zeaxanthin to lutein ratios are reported for groups at risk of age-related macular degeneration (e.g., the elderly and females) [74]. A number of studies, including some in healthy subjects, have demonstrated that lutein/zeaxanthin supplementation can improve visual performance, including contrast sensitivity, glare tolerance and photo stress recovery [65,66,67,68,69,70,71,72,75,76].…”
Section: Eye Disordersmentioning
confidence: 99%
“…The previous study stated that supplementation with carotenoids such as zeaxanthin (2 mg/day/year) and lutein (10–20 mg/day/year) can increase macular pigment optical density levels [104,105]. Several studies reported by Hammond et al [104] and Nolan et al [106] also showed that zeaxanthin/lutein (2 mg/10 mg/day/year) can enhance visual performance such as photostress recovery, glare tolerance, and contrast sensitivity. Collectively, carotenoid intake could be a potential approach for the amelioration of oxidative stress and provide potential benefits for ocular health and function.…”
Section: The Role Of Carotenoids In the Prevention Of Ardmentioning
confidence: 99%